Fighting Corruption Through Tax Administration Reform: Vietnam Case Study - Thao Le thi (LEGAL BRIEF, 2023)
Corruption in tax administration is attracting much attention worldwide due to its strong negative impact on economic activity, especially impact on tax revenue and budget deficit. Corruption erodes trust and causes loss of state budget revenue, especially in the tax field. In the process of digital transformation with many reforms in the tax administration mechanism in Vietnam, corruption in tax administration has been somewhat limited. This study is based on political and legal analysis by normative method or theoretical legal research, taking Vietnam as research evidence. On the basis of the current status of Vietnam's tax administration mechanism in the past time, identifying corrupt acts in the tax administration process through tax management practices, the research results show that tax administration with current The modernization of tax administration is the basic basis to limit corruption in the tax field. With the reform of tax administration by simplifying tax processes and procedures, reducing the arbitrary situation and abuse of tax laws by tax officials, transferring the entire tax collection function to modern tax management - a modern tax administration is needed to keep up with the growing trend. the complexity of the operations of companies in the age of globalization.